Tingkat pendidikan menurunkan risiko hipertensi - Putu Suriyasa (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Hypertension is an important problem because of its high incidence and prolonged risk for organs like the heart, vessels, kidneys and retina. Risk factors of hypertension include age, socioeconomical conditions, biology and behavior. The Ministry of Health of the Republic of Indonesia has designed a simple indicator to evaluate the family health potentials, the Family Health Potential Index (FHPI). This study aims to evaluate the effect of FHPI and other indicators on the risk of hypertension. Methods: The data were obtained through a survey carried out by a team from the Family Physician Studies, Graduate Program of the Sebelas Maret University. The survey was held from August to September 2003 in 5 provinces receiving the Family Health and Nutrition (FHN) project. The subjects were 1500 heads of families chosen by stratified random sampling. Interviews and observations were carried out by specially trained interviewers and held in the subjects' homes. Results: In the study location it has been found that formal education is a hypertension risk. Elementary School has lowered the risk of hypertension by 66% [(adjusted odds ratio (OR)=0.34; 95% Confidence Interval (CI)=0.14-0.80, p=0.014)], Junior High School has lowered the risk of hypertension by 72% when compared with no schooling (OR=0.28; 95% CI = 0.09-0.87, p=0.028). People of Central Kalimantan need special attention to reduce risk of hypertension. It is related with high risk of hypertension in Central Kalimantan which is more than by 3,7 times compared with North Sumatera (OR=3.73;95C1=1.22-11.4). Conclusion: Education can decrease risk of hypertension. Better education lowers risk of hypertension. Keywords: hypertension, education and province